2012
DOI: 10.1159/000342635
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 17�-Oestradiol on Increased a1-Adrenergic Vascular Reactivity Induced by Prolonged Ovarian Hormone Deprivation: The Role of Voltage-Dependent L-type Ca2+Channels

Abstract: The present study investigated the hypothesis that the duration of ovarian hormone deprivation before reintroduction of oestrogen affects the role of oestrogen as a mediator of the contractile function of α1-adrenergic receptors. Rats underwent ovariectomy (OVX) or were sham-operated, and the OVX rats were treated with vehicle (corn oil) or 17β-oestradiol (E2) for 5 days either 10, 28 or 60 days after OVX. The OVX increased phenylephrine- and Ca2+-induced contractions. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Our results showed an increase in Ca +2 channel reactivity in aortic rings at 10- but not 20-week postovariectomy. In agreement with our results, Valencia-Hernández et al demonstrated that Ca 2+ vascular reactivity in ovariectomized female rats depends on the postovariectomy time, finding an increase in Ca 2+ response at 8 weeks, but not at 1 or 3 weeks after the surgery [78]. Kim and Yang also found an increase in K Ca channel conductance two weeks after ovariectomy [79].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed an increase in Ca +2 channel reactivity in aortic rings at 10- but not 20-week postovariectomy. In agreement with our results, Valencia-Hernández et al demonstrated that Ca 2+ vascular reactivity in ovariectomized female rats depends on the postovariectomy time, finding an increase in Ca 2+ response at 8 weeks, but not at 1 or 3 weeks after the surgery [78]. Kim and Yang also found an increase in K Ca channel conductance two weeks after ovariectomy [79].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, 17␤E-mediated regulation of VGCC also depends on the timing of initiation of 17␤E treatment. Animals treated with 17␤E for 10, 28, and 60 days after OVX increased VGCC-mediated contraction in the 10-day treatment group, whereas there was no change in VGCC-mediated contraction with 28-and 60-day treatment, highlighting the importance of the timing hypothesis (248). Overall, these studies suggest that 17␤E, via genomic and nongenomic actions, can regulate VGCC ␣and ␤-subunit expression and function and, furthermore, that these actions depend on the time of initiation of 17␤E treatment.…”
Section: ␤E Decreases Ca 2؉ Channel Expression and Functionmentioning
confidence: 93%